1990
DOI: 10.2307/1242630
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the von Liebig and Differentiable Crop Production Functions

Abstract: Two commonly used forms for crop response to inputs are a smooth, differentiable production function and a linear response and plateau (LRP) model. This paper reconciles these two views by showing that smooth functions can be derived by aggregating the effects of heterogenous inputs on LRP functions. Data on com growth are used to test two specific aggregations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
8

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 16 publications
(1 reference statement)
1
73
0
8
Order By: Relevance
“…Following Berck and Helfand (1990), Paris (1992), Chambers and Lichtenberg (1996), and Berck, Geoghegan and Stohs (2000), the production technology is modeled as of the von-Liebig type:…”
Section: With ( )mentioning
confidence: 99%
“…Following Berck and Helfand (1990), Paris (1992), Chambers and Lichtenberg (1996), and Berck, Geoghegan and Stohs (2000), the production technology is modeled as of the von-Liebig type:…”
Section: With ( )mentioning
confidence: 99%
“…Although an individual vessel's fishing trip is likely to have a fixed-proportions technology, there is significant variation across vessels (for example, in captain experience, age of vessel, etc.). These non-conformities may be used to justify the use of a smooth function to approximate an aggregate production function (Berck et al, 1988). Additionally, it can be shown that the Tornqvist index is exact for the generalized Leontief production function (Chambers, 1988).…”
Section: Empirical Investigationmentioning
confidence: 99%
“…Beginning in 1909, the works of Mitscherlich [7] and independently from 1923 works of Spillman [8] offered a model (productivity functions of Mitscherlich-Spillman PFMS) based on the inverse exponent, which has also a plateau as productivity function of Liebig, but it has damped response within the break point. Further development of theoretical concepts of the FP was made by Baule in 1918 (multifactor model of Mitscherlich-Baule [9]), Bray since 1944 (the concept of influence of mobility of food compounds on PF [10][11][12], Von Boguslawski E., & B. Schneider, refinement of Mitscherlich model [13][14][15][16] and many other researchers [2][3][4][17][18][19][20][21][22][23][24][25][26][27][28][29]. It is necessary to recognize the technical complexity of calibration of PFMS, especially for two or more variables.…”
Section: Introductionmentioning
confidence: 99%